Pengaruh Key Opinion Leader, Trustworthiness Dan Risk Perception Terhadap Minat Beli Konsumen Produk Kecantikan Ms Glow - Ilmi, Lutfia Warkhamna Mujizatul; Mahendri, Wisnu (CV. ITTC INDONESIA, 2023)
This research aims to determine the influence of key opinion leader (KOL), trustworthiness, risk perception on interest in buying MS Glow products online. The subject in this research is interest in buying MS Glow products online, and the objects are key opinion leader (KOL), trustworthiness, risk perception. The location of this research is Jombang Regency. The determination of this location was considered based on the widespread sales of MS Glow in Jombang Regency, for this reason the author is interested in further researching how current forms of marketing are able to influence their views or attitudes towards a brand on the market. The sampling method used was non-probability sampling and data collection used purposive sampling. Data was collected using a questionnaire where a sample of 100 respondents was taken. The type of research in this research is descriptive quantitative research using multiple linear regression analysis, coefficient of determination, partial test (T test), and simultaneous test (F test). The results of this study show that the key opinion leader variable (X1), the trustworthiness variable (X2) and the risk perception variable (X3) partially (T Test) have a positive and significant influence on consumer buying interest, while simultaneously (F Test) the variables key opinion leader (X1), trustworthiness variable (X2) and risk perception variable (X3) have a positive and significant influence on consumer buying interest (Y). With the Adjusted R-Square, the result is 60.2% and the remaining 39.8% is influenced by other variables.